Analysis of Deck Slab of Reinforced Concrete Gerber-Girder Bridge Widened by Addition of Continuous Steel-Concrete Composite Girders - Wojciech Siekierski (The Baltic Journal of Road and Bridge Engineering)
Many Gerber-girder bridges have become obsolete in terms of deck width and load carrying capacity. If bridge replacement is not necessary, additional girders are installed. Sometimes, due to erection convenience, the added girders do not replicate the static scheme of the refurbished structure. Such an arrangement requires special attention to preserve structural durability. An example of the inappropriate arrangement of the widening of a Reinforced Concrete Gerber-girder road bridge is presented together with an alternative concept of refurbishment based on the addition of the continuous steel-concrete girders as the outermost ones. The added deck slab connects the added and the existing parts of the structure. Attention is drawn the static analysis of the added deck slab and the influence of the added outermost girders that do not replicate the static scheme of the existing ones. Due to different static schemes of the existing and the added girders, the traditional method of the deck slab analysis is inappropriate. The Finite Element 3D model is to be applied to access bending moments in the deck slab spans correctly. It is shown that: a) the analysis of the distribution of the bending moments in the existing and the added slab spans, especially near Gerber-hinges, should be based on the Finite Element 3D modelling; b) the analysis should consider live loads acting on the whole width of the Gerber-hinge span; c) the bending moment distribution in the widened deck slab is sensitive to the distance to the Gerber hinge.